Dampak Adanya Pertumbuhan Eceng Gondok dalam Skala Besar Terhadap Ekosistem di Kawasan Danau Toba - Sartika Tobing, Nisa; Hayati Harahap, Rahma (STISIPOL Raja Haji, 2024)
Lake Toba, as one of Indonesia's natural wonders, is experiencing serious challenges related to environmental damage and water pollution caused by the large-scale growth of water hyacinth. The growth of water hyacinth is the result of irresponsible human activities, such as the disposal of domestic, industrial, agricultural and other waste that enriches nutrients in lakes. The aim of this research is to investigate the impact of large-scale water hyacinth growth in Lake Toba on the lake ecosystem. By using B.F.'s behavioral theory. Skinner as a framework, this research identifies human behaviors that contribute to water hyacinth growth and evaluates interventions that may be needed to address this problem. The research method used is library and literature study, with behavioral theory analysis to understand the relationship between stimulus and response in the context of water hyacinth growth. The research results show that human behavior, such as waste disposal and daily activities, plays an important role in the growth of water hyacinth in Lake Toba. The negative impacts of growing water hyacinth include decreasing water quality, increasing nutrient content, and disturbing animal life in the lake. By better understanding the factors that influence the growth of water hyacinth and its impacts, it is hoped that more effective interventions can be designed to maintain the sustainability of the Lake Toba ecosystem.